1985
DOI: 10.1182/blood.v66.5.1053.1053
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of involvement of the B and T lymphocyte lineages in chronic myelogenous leukemia

Abstract: Peripheral blood specimens were obtained from 22 patients with Philadelphia chromosome (Ph1) positive chronic myelogenous leukemia (CML) (16 in chronic phase, 2 in an accelerated phase, and 4 in blast crisis). Studies were performed to determine the frequency of the presence of the Ph1 chromosome in cells of lymphoid lineages. Rosetted (E+) lymphocytes (T lymphocytes) from nine patients in chronic phase and one patient in blast crisis were stimulated with T cell growth factor interleukin 2 (IL-2) and/or phytoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(14 citation statements)
references
References 75 publications
0
13
0
1
Order By: Relevance
“…Alternatively, and in view of our in vitro results, the causes of DC reduction may be central, with a decreased production of DC from primitive haematopoietic stem cells. Different lines of evidence placed the malignant transformation in CML closer to, if not in, the pluripotential stem cell (Nitta et al , 1985). Therefore, ‘dendritopoiesis’ in CML is likely to be affected by the leukaemic process that induces a marked expansion of granulopoietic progenitors to the detriment of other populations.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, and in view of our in vitro results, the causes of DC reduction may be central, with a decreased production of DC from primitive haematopoietic stem cells. Different lines of evidence placed the malignant transformation in CML closer to, if not in, the pluripotential stem cell (Nitta et al , 1985). Therefore, ‘dendritopoiesis’ in CML is likely to be affected by the leukaemic process that induces a marked expansion of granulopoietic progenitors to the detriment of other populations.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic myelogenous leukemia is a myeloproliferative disease, and whether the lymphoid lineages are part of the clonal disorder has been a matter of controversy (29–31). As expected, a relative number of CD34 + CD33 + cells increased in CML.…”
Section: Discussionmentioning
confidence: 99%
“…19,[100][101][102][103] The presence of the Ph chromosome in erythrocyte, granulocyte, monocyte, and megakaryocyte precursors indicates that the original transformation occurred in an ancestral stem cell common to these cell types; it is absent in the majority of mature lymphocytes, although in about 20-25% of patients in chronic phase some of the B cells contain the Ph marker and early B-cell progenitors predominate in about 25% of patients in blastic transformation. 73,74,78,104 However, the level of expression of p210 bcr-abl in Epstein-Barr virus transformed B-cell lines that retain Bcr-Abl is lower and more variable than in myeloid cell lines derived from patients in blastic phase 105 T-lymphocytes have only rarely been found to be Ph+ either during the chronic or blastic phases of the disease, 106,107 but bilineal (T lymphoid/myeloid) Ph+ progenitors may be involved in some cases of blastic transformation, 108 and quadralineal involvement was reported in one patient with Ph+ ALL. 109 It was recently reported that variable proportions of endothelial cells in CML patients contain the Bcr-Abl fusion gene, suggesting that they may be derived from a common hemangioblastic progenitor cell 110 .…”
Section: Introductionmentioning
confidence: 99%